Nonparallel nephrotoxicity dose-response curves of aminoglycosides. - Hottendorf, G H (1981)
Nephrotoxicity comparisons of aminoglycosides in rats, utilizing large multiples of human doses, have indicated an advantage for netilmicin. However, no nephrotoxicity advantage of netilmicin has been demonstrated at the lower doses used in clinics. Some high-dose studies in rats have also suggested that the slope of the nephrotoxicity dose-response curve of netilmicin was less steep than the slopes of other aminoglycosides. Therefore, the slopes of the nephrotoxicity dose-response curves of gentamicin, amikacin, and netilmicin were compared in 200 rats at low multiples (one to five times) of human clinical doses. Histopathological evaluations of both kidneys from each rat revealed that netilmicin produced equivalent or greater nephrotoxicity as compared with gentamicin and amikacin and that the slope of the nephrotoxicity dose-response curve of netilmicin was approximately one-half as steep as the slopes of amikacin and gentamicin, which were parallel. The distribution of casts excreted in the urine after 2 weeks of dosing and the terminal gross observations corroborated the flatter dose-response slope of netilmicin. Nephrotoxicity advantages predicted by high-dose comparisons with netilmicin in rats are apparently a function of its less steep dose-response slope and therefore may have no relevance to lower doses.